Removal of halogenated emerging contaminants from water by nitrogen-doped graphene decorated with palladium nanoparticles: Experimental investigation and theoretical analysis. (1st July 2016) - Li, Lei; Gong, Li; Wang, Yi-Xuan; Liu, Qi; Zhang, Jie; Mu, Yang; Yu, Han-Qing
Abstract: The removal performance and mechanisms of halogenated emerging contaminants from water by palladium decorated nitrogen-doped graphene (Pd/NG) were investigated in this study. For comparison, three catalysts of Pd/NG, palladium decorated graphene (Pd/G) and commercial Pd/C were initially explored to degrade tetrabromobisphenol A (TBBPA). After that, the influence of various environmental parameters on TBBPA removal by the Pd/NG catalyst was evaluated. Moreover, both Langmuir–Hinshelwood model and density functional theory (DFT) were adopted to theoretically elucidate the adsorption and the activation of TBBPA on the catalyst. The results show that the apparent rate constant of TBBPA dehalogenation was increased by 26.7% and 39.0% in the presence of the Pd/NG catalyst compared to the Pd/G and Pd/C ones. Higher temperature, catalyst dosage and alkaline conditions resulted in the enhancement of TBBPA dehalogenation by the Pd/NG catalyst, while humic acid in the solution had a negatively effect on the transformation of TBBPA. The corresponding rate constant value exhibited a 2.1- and 1.8-fold increase with the rise of temperature from 298 to 328 K and initial pH from 6.5 to 9.0, respectively. On the contrary, the rate constant was decreased by 78.9% in the presence of 15 mg L −1 humic acid. Theoretical analysis revealed that both adsorption and activation processes of TBBPA on the Pd/NG catalyst were enhanced through the N doping into graphene framework. Graphical abstract: Highlights: Better performance of Pd/NG for removing halogenated emerging contaminants from water. Environmental factors substantially affected the TBBPA dehalogenation by Pd/NG. Adsorption and activation of TBBPA on Pd/NG surface were enhanced through N doping. TBBPA and TCS were rapidly removed by Pd/NG even at a concentration of 10 μg L −1 .